2007
DOI: 10.1523/jneurosci.0108-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila HyperkineticMutants Have Reduced Sleep and Impaired Memory

Abstract: In mammals, sleep is thought to be important for health, cognition, and memory. Fruit flies share most features of mammalian sleep, and a recent study found that Drosophila lines carrying loss-of-function mutations in Shaker (Sh) are short sleeping, suggesting that the Sh current plays a major role in regulating daily sleep amount. The Sh current is potentiated by a ␤ modulatory subunit coded by Hyperkinetic (Hk). Here, we demonstrate that severe loss-of-function mutations of Hk reduce sleep and do so primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 50 publications
9
133
0
2
Order By: Relevance
“…The decreased expression of neuronal genes in the adult brain prompted us to test whether the loss of CDK12 or CycK would have any effect on neuronal behaviors. Because the potassium channel genes Sh, Hk, eag, and SK and the cAMP phosphodiesterase dnc are all known to be involved in Drosophila learning and memory (19,(22)(23)(24)(25), we performed a courtship conditioning test using an OK107-GAL4 driver, which is mainly active in the MBs (putative learning and memory centers in the Drosophila brain). Unsuccessful courtship reduces the subsequent courtship behavior of male flies toward virgin females, and this courtship conditioning behavior is known as one of the major learning and memory paradigms in Drosophila.…”
Section: Heterochromatin Enrichment On Cdk12 Depletion Affects Drosopmentioning
confidence: 99%
“…The decreased expression of neuronal genes in the adult brain prompted us to test whether the loss of CDK12 or CycK would have any effect on neuronal behaviors. Because the potassium channel genes Sh, Hk, eag, and SK and the cAMP phosphodiesterase dnc are all known to be involved in Drosophila learning and memory (19,(22)(23)(24)(25), we performed a courtship conditioning test using an OK107-GAL4 driver, which is mainly active in the MBs (putative learning and memory centers in the Drosophila brain). Unsuccessful courtship reduces the subsequent courtship behavior of male flies toward virgin females, and this courtship conditioning behavior is known as one of the major learning and memory paradigms in Drosophila.…”
Section: Heterochromatin Enrichment On Cdk12 Depletion Affects Drosopmentioning
confidence: 99%
“…[10][11][12] In Drosophila and mouse models, genetic mutants exhibiting reduced sleep also show impairments in memory. [13][14][15] However, increasing sleep, either pharmacologically or genetically, can enhance learning and memory in suboptimal situations. 16,17 Neither the effects of sleep deprivation nor the role of sleep in the induction and consolidation of memories are well understood at the neuronal or molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in Drosophila has demonstrated that knockdown of Cdk1 significantly reduces seizure duration in both bang sensitive (bas) and bang senseless (bss) mutants, 25 27 slow delayed rectifier potassium channel, 28 nicotinic acetylcholine receptor, 29 and GABA A receptor, 30,31 respectively, are all implicated in sleep and may be potential phosphorylation targets of Cdk1.…”
mentioning
confidence: 99%